Relationship Between Multimorbidity, Nutritional Status and Duration of ARV Treatment to Major Signs of HIV at RSUD Dr. Soetomo Surabaya - Kartika Alifia; Hartati Eko Wardani; Tika Dwi Tama; Anindya Hapsari; Rara Warih Gayatri (Research and Development Center for Food, Nutrition and Public Health (P4GKM) LPPM UNS, 2024)
People living with HIV/AIDS (PLWHA) can have better health outcomes with early identification of the AIDS phase. In the first three years, PLWHA may progress to the AIDS stage. This cross-sectional study aimed to determine the relationship between multimorbidity, nutritional status and duration of Antiretroviral (ARV) treatment on major signs of PLWHA. This study was conducted in the Intermediate and Infectious Disease Treatment Unit (UPIPI) at regional public hospital (RSUD) Dr. Soetomo Surabaya from January to February 2023. As many as 52 PLWHA who started HIV treatment at RSUD Dr. Soetomo in 2020 to 2021 were sampled in this study, which was obtained from medical records. The dependent variable in this study was the major sign of HIV. Independent variables in this study were multimorbidity, nutritional status, and the duration of ARV treatment. This study found that 76.9% of PLWHA experienced major signs. Multimorbidity and duration of ARV treatment did not have an association with major signs of HIV (p-value > 0.05). Nutritional status has a significant association with major clinical symptoms of HIV (p-value < 0.05). PLWHA with underweight had higher odds of having a major sign (p-value = 0.017; PR = 1.507; 95% CI 1.131-2.008) than PLWHA with normal nutritional status. Thereby, it is hoped that the hospital will be assisted in determining health promotion needs such as screening and evaluation of nutritional status to monitor the nutritional status of patients, which will improve their health outcomes.